Purificação e Estudo Farmacológico da Atividade PróInflamatória de um Fator Extraído da Pele de Leptodactylus labyrinthicus (Spix,1824) - Mota, Maria Lurdemiler Sabóia (1999)
The amphibian skin synthesizes several biologically active substances. These substances resemble mediators of mammals and are used as phannacological tools for studies of the physiologic fimctions in this class. This study consists on evaluating the ability of these substances, extracted from the skin offrog (Leptodactylus labyrinthicus), to induce inflammation in rat and to determine the mechanisms involved on it. Extract of skin were submitted to a reverse-phase high performance cromatography and tested in classical inflammation models: rat paw edema, inflammation in peritoneal cavities and increase of vascular permeability measured by Evans blue extravazation. Our results demonstrated that the poison extract, as well as all fractions (Fr), exception the ffaction 14, were capable to induce edema (p<0,05) 30 minutes after the subplantar injection, with peak activity at 1 hour. It was choose the Fr 5, which molecular weight determined by this study, was about 2490 D, to continue the investigation. Histamine and bradykinin antagonists blocked partially, even so significantly (p <0,05) the paw edema induced by Fr 5. Serotonine antagonist was more efícient in inhibiting that edema. The cypro-heptadin that is antagonist of the three substances, inhibited the edema induced by Fr 5 almost completely. Antagonist selective for phospholipase A2 was capable to inhibit significantly (p <0,05) just the peak of the paw edema induced by Fr 5. Dexamethasone inhibited significantly (p <0,05) and in a dose-dependent way, the paw edema induced by this fraction in the precocious and late phases. Antagonist selective for lipoxygenase also inhibited this edema (p <0,05) in several points of the curve, the same not happened with ciclooxygenase antagonist, indomethacin that was not capable to inhibit it. Furthermore, Fr 5 was capable to signifícantly (p <0,05) induces ipast cell degranulation in in vitro and in vivo models. Fr 5 induced signifícant eosinophil migration (p <0,05) and a discreet, but also sigiifícant neutrophil migration, besides signifícant increase of vascular permeability to tlie peritoneal cavity whose peak, coincided with the peak of the mast cell degranulation. The data suggest that the increase in vascular permeability, eosinophil and neutrophil migration induced by Fr 5 is mediated by substapces originating ffom ofthe activation and/or mast cell degranulation. The discovery ofsubstances like Fr 5, whose action seems to occur in a specifíc stage of the allergic process and the use of experimental animal models may be tools of great value for the understanding of the allergic processes phisiopathology